Analysis And Design of Internet Network Infrastructure With Mikrotik Devices At The Penyaring Village Office Using The NDLC Method - Yunanri. W.; Yasinta Bella Fitriana; Rizky Andhika Surya (Brilliance: Research of Artificial Intelligence, 2023)
Communication and Internet technology are developing very rapidly, one of which is in the field of telecommunications technology and is directly proportional to the public's need for its use and also with the increasing need for fast and efficient services both in agencies, commercial, academic worlds and in the homes of residents who need internet access. Thus making telecommunications technology an inseparable technology to support human work. The Penyaring Village Office is located in North Moyo District, Sumbawa Regency, which is the center for all activities in the Village, both in the fields of government, empowerment, development, and coaching, all of which are centered at the Penyaring Village office. This research aims to analyze and design the internet network in the Penyaring Village office and prevent slow wifi so that the network stability in the Penyaring Village office becomes more stable/smooth when used, and the work in the Penyaring Village office becomes better and optimal. This research uses Router, Mikrotik, Access Point network devices, Winbox software, and other supporting devices. The network development method uses the NDLC (Network Development Life Cycle) method, which begins with the Analysis, Design, Simulation Prototype, Implemetation, Monitoring and Management. The research method uses qualitative consisting of observation, interviews, and documentation. The results of this research are building network infrastructure, network security, and bandwidth distribution in each sector which can stabilize the process of using WiFi at the Penyaring Village Office.